2003
DOI: 10.1111/1467-9280.03453
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceptual Load in Processing Distractor Faces

Abstract: It has been established that successful ignoring of irrelevant distractors depends on the extent to which the current task loads attention. However, the previous load studies have typically employed neutral distractor stimuli (e.g., letters). In the experiments reported here, we examined whether the perception of irrelevant distractor faces would show the same effects. We manipulated attentional load in a relevant task of name search by varying the search set size and found that whereas congruency effects from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
285
14
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(353 citation statements)
references
References 24 publications
(34 reference statements)
38
285
14
4
Order By: Relevance
“…For instance, numerous behavioural studies have examined the relationship between visual perceptual load and the magnitude of the flanker compatibility effect (Eriksen and Eriksen, 1974). These studies have shown that as the perceptual load associated with the target is increased, the magnitude of the flanker compatibility effect is reduced or even eliminated altogether (Lavie, 1995;Lavie and Cox, 1997;Lavie et al, 2004;Lavie et al, 2003), consistent with the notion that increasing perceptual load reduces involuntary processing of unattended flanker items. Further evidence Crossmodal perceptual load 4 comes from studies using functional magnetic resonance imaging (fMRI) to measure the magnitude of blood-oxygen-level dependent (BOLD) responses to unattended visual stimuli under varying levels of visual perceptual load.…”
Section: Introductionmentioning
confidence: 81%
“…For instance, numerous behavioural studies have examined the relationship between visual perceptual load and the magnitude of the flanker compatibility effect (Eriksen and Eriksen, 1974). These studies have shown that as the perceptual load associated with the target is increased, the magnitude of the flanker compatibility effect is reduced or even eliminated altogether (Lavie, 1995;Lavie and Cox, 1997;Lavie et al, 2004;Lavie et al, 2003), consistent with the notion that increasing perceptual load reduces involuntary processing of unattended flanker items. Further evidence Crossmodal perceptual load 4 comes from studies using functional magnetic resonance imaging (fMRI) to measure the magnitude of blood-oxygen-level dependent (BOLD) responses to unattended visual stimuli under varying levels of visual perceptual load.…”
Section: Introductionmentioning
confidence: 81%
“…Some nontarget visual stimuli have been shown to be prioritized for processing even while performing high-load tasks, and may draw on participant-specific backgrounds. Lavie, Ro, and Russell (2003) and He and Chen (2010) both showed that RTs to categorize centrally presented words in high-load searches were influenced by peripherally presented faces that were strongly related to the words. In addition, Ro, Friggel, and Lavie (2009), using a task similar to Lavie et al (2003), demonstrated that prior experience can impact attention control settings when processing nonface visual stimuli.…”
Section: Greater Influence Of Crossmodal Stimuli Under High Loadmentioning
confidence: 97%
“…Lavie, Ro, and Russell (2003) and He and Chen (2010) both showed that RTs to categorize centrally presented words in high-load searches were influenced by peripherally presented faces that were strongly related to the words. In addition, Ro, Friggel, and Lavie (2009), using a task similar to Lavie et al (2003), demonstrated that prior experience can impact attention control settings when processing nonface visual stimuli. When expert musicians classified centrally presented words as naming one of two types of musical instruments presented in high-load searches, their RTs were influenced by peripherally presented pictures of musical instruments that varied in congruity with the target word.…”
Section: Greater Influence Of Crossmodal Stimuli Under High Loadmentioning
confidence: 97%
See 1 more Smart Citation
“…Several recent studies demonstrated that faces constitute a class of stimuli that are especially prone to capture attention (Bindemann, Burton, Hooge, Jenkins, & de Haan, 2005;Lavie, Ro, & Russell, 2003;Theeuwes & Van der Stichgel, 2006). However, few studies evaluated whether one's own face, because of its self-significance, is more likely to draw attention than other faces.…”
Section: Own Facementioning
confidence: 99%